1991
DOI: 10.1288/00005537-199103000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Detection of epstein‐barr virus DNA in formalin‐fixed paraffin‐embedded tissue of nasopharyngeal carcinoma using polymerase chain reaction and in situ hybridization

Abstract: The polymerase chain reaction method for amplification of DNA in formalin-fixed, paraffin-embedded tissue sections was used to detect Epstein-Barr virus DNA in nasopharyngeal carcinomas from Japanese patients. Thirty-one cases of nasopharyngeal carcinoma and 8 cases of lymph node metastasis of nasopharyngeal carcinoma were studied. Detection rates of Epstein-Barr virus in various types of nasopharyngeal carcinoma according to the World Health Organization classification were as follows: 10 of 10 undifferentiat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
17
0

Year Published

1993
1993
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(18 citation statements)
references
References 20 publications
1
17
0
Order By: Relevance
“…The presence of the EBV genome in the differentiated forms of NPC was recently reported. 17,18) We confirmed this in the present study; i.e., the EBV genome was also found in the tumor cells of moderately and well-differentiated SCC, though much less frequently than in the poorly differentiated form. The stable maintenance of EBV in epithelial cells of undifferentiated condition was reported by Knox et al 19) This might be one of the reasons for the high EBV-association in NPC.…”
Section: Discussionsupporting
confidence: 89%
“…The presence of the EBV genome in the differentiated forms of NPC was recently reported. 17,18) We confirmed this in the present study; i.e., the EBV genome was also found in the tumor cells of moderately and well-differentiated SCC, though much less frequently than in the poorly differentiated form. The stable maintenance of EBV in epithelial cells of undifferentiated condition was reported by Knox et al 19) This might be one of the reasons for the high EBV-association in NPC.…”
Section: Discussionsupporting
confidence: 89%
“…However, the evidence regarding the possibility of an EBV association with keratinizing squamous cell NPC has been conflicting. The studies from Raab-Traub et al [1987] and other laboratories [Pathmanathan et al, 1995;Chen et al, 1993;Dickens et al, 1992;Akao et al, 1991] indicated that keratinizing NPC from Asian patients are associated regularly with EBV. But Niedobitek et al [1991] failed to detect the virus in such tumours from Caucasian patients, and similar observation were also obtained from some other groups [Hording et al, 1993;Nicholls et al, 1997;Klein et al, 1974].…”
Section: Discussionmentioning
confidence: 99%
“…Virus-related pathologies can occur, however, and are of particular concern in immunocompromised individuals (4,5,48). EBV is associated with the development of several malignancies, including Burkitt's lymphoma, Hodgkin's lymphoma, nasopharyngeal carcinoma, and various lymphoproliferative disorders arising in immunocompromised patients (2,3,4,15,37,74).…”
mentioning
confidence: 99%